Dyads Versus Groups: Using Different Social Structures in Peer Review to Enhance Online Collaborative Learning Processes - Pozzi, Francesca; Ceregini, Andrea; Ferlino, Lucia; Persico, Donatella (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
The Peer Review (PR) is a very popular technique to support socio-constructivist and connectivist learning processes, online or face-to-face, at all educational levels, in both formal and informal contexts. The idea behind this technique is that sharing views and opinions with others by discussing with peers and receiving and providing formative feedback enriches the quality of learning. In this study, a class of trainee teachers conducts an online PR. The resulting interactions are analyzed and evaluated by the researchers through the application of an evaluation model based on both quantitative and qualitative data. In particular, two conditions are studied, namely the PR in groups versus the PR in dyads. Results show that students who carried out the PR in groups were less active from the cognitive point of view, while they devoted more effort to deal with organizational matters and discourse facilitation.